2000
DOI: 10.2307/2657461
|View full text |Cite
|
Sign up to set email alerts
|

Family Change, Employment Transitions, and the Welfare State: Household Income Dynamics in the United States and Germany

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. American Sociological Association is collaborating with JSTOR to digitize, preserve and extend access to American Sociological Review.Since the demise of modernization theory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
160
0
7

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(177 citation statements)
references
References 24 publications
10
160
0
7
Order By: Relevance
“…Early unemployment has been found detrimental for workers' future employment opportunities because it reduces the future likelihood to be hired, and inflicts a setback in re-employment wages that perpetuates long after the initial unemployment occurrence (Arulampalam, 2001;DiPrete, 1981;DiPrete and McManus, 2000;Gangl, 2004Gangl, , 2006Gregg, 2001;Jacobson et al, 1993;Kuhn, 2002;Moore, 2010;Ruhm, 1991). This wage setback is referred to in the literature as 'unemployment scarring'.…”
Section: Introductionmentioning
confidence: 99%
“…Early unemployment has been found detrimental for workers' future employment opportunities because it reduces the future likelihood to be hired, and inflicts a setback in re-employment wages that perpetuates long after the initial unemployment occurrence (Arulampalam, 2001;DiPrete, 1981;DiPrete and McManus, 2000;Gangl, 2004Gangl, , 2006Gregg, 2001;Jacobson et al, 1993;Kuhn, 2002;Moore, 2010;Ruhm, 1991). This wage setback is referred to in the literature as 'unemployment scarring'.…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary research aims in particular at analysis of the income development dynamics, its stability, and detection of important factors affecting the income levels. Some works concentrated on the description of income development dynamics are Paap andvan Dijk (1998), Di Prete andMcManus (2000); its stability in EU countries is considered in Longford and Pittau (2006). The articles by Kneip and Utikal (2001), and Pittau (2004) focus on identification of the most influential factors and regional diversities in the EU.…”
Section: A D V a N C E D M E T H O D S O F A N A L Y S I S A N D M mentioning
confidence: 99%
“…Results from DiPrete and McManus (2000) show that German women tend to recover faster than American women from union dissolution, though this recovery is from a more negative position, and only allows German women to achieve parity with American women after several years (table 4, rows 5a, 5b, 5c, and 5d). Results from Ruspini (1998) suggest that German women do not repartner as fast as Swedish women (table 4, row 6).…”
mentioning
confidence: 99%
“…DiPrete and McManus (2000) found that the mean loss two years after a union dissolution in adjusted (for household size) household income was 25% for American women, and 32% for western German women. Here I instead use the above simulation to estimate the impact of union dissolution on entry into poverty, defined in the conventional (for international comparisons) way as 50% of the median income of a society.…”
mentioning
confidence: 99%
See 1 more Smart Citation